Peningkatan Sikap Keluarga Tentang Perawatan Pasca Stroke Setelah Diberikan Health Education - Andi Parellangi (MNJ (Mahakam Nursing Journal), 2016)
Abstract Background: Stroke patients from year to year increasing and become the second cause of death in the world. Family’s attitudes of patient care can be influential on the health of the patient stroke. Purpose: Identify influence of health education to enhancement family attitudes about post-stroke treatment. Methods: This study using quasi-experiment research with Pre test and post test nonequivalent control group design. The Population of this study is all the family who has family members who registered in Home care Cahaya Husada Kaltim. The determination of samples based on the criteria of inclusion until the number of samples of least fulfilled. Samples divided into two groups which are treatment and control. The number of samples every group is 30 respondents. Pre-test held before the intervention and then post test will be held after the intervention. The data had been collected analyzed with paired sample t-test. Results: This study show that health education have contribution as big as 92,74% to increase family attitudes about post-stroke treatment with value p value = 0,000 <0,05 is that mean there are significant differences respondent’s attitudes before and after given health education. Conclusions: There is an increase in family attitudes about post-stroke treatment after given intervention health education. Keywords: health education, attitude, stroke